Aprendizagem e desenvolvimento na perspectiva da Psicologia Histórico-Cultural: implicações para o trabalho na área da Psicopedagogia Escolar - Souza, Elenice de (2024)
This master's research investigated the contributions of the Historical-Cultural Theory (HCT) to work in School Psycho-pedagogy. This research is considered important because of the lack of scientific productions referring to the School Psycho-pedagogy Service based on this theoretical basis and the fact that the municipality investigated has had a psycho-pedagogue in 31 of the 36 schools that make up the municipal education network for approximately 20 years. An action research project carried out in 2018 is described, which, using questionnaires answered in person, with open and closed questions, sought to understand the contributions of the evaluation carried out by the school psycho-pedagogue to the pedagogical practice in the regular education classroom, considering the role of assessment in the school context. The results of this research indicated important inconsistencies. Despite the time that has elapsed, given the relevance and topicality of its subject, and the fact that it involved 239 teachers, 16 pedagogical coordinators, and 16 psycho-pedagogues, covering 50% of the schools in the municipality investigated, it was considered important in this dissertation to give a scientific treatment to the data already collected in 2018, using percentage calculations, the Content Analysis proposed by Bardin and the Dynamic-Causal Method enunciated by Vygotsky. The results were analyzed based on the contributions of Historical-Cultural Theory, reflecting on the relationships between human genericity from the categories of analysis defined by the Dynamic-Causal Method, considering the use of instruments and signs, higher psychological functions, zone of imminent development, to explain the social nature of the human psyche and its implications for school psycho-pedagogical action, involving assessment, intervention and its institutional performance. Next, we analyzed the Work Proposal for the Toledo Psycho pedagogy Service, drawn up in 2020, resulting from the work carried out from the 2018 action research, seeking to highlight its inconsistencies and gaps. It is concluded that it is important for the school psychologist's work, in addition to assessing students with delayed school development, to consider the objective conditions necessary for learning, considering the developmental guide activities proposed by Historical Cultural Theory. It is proposed that the work of the school psycho-pedagogue should extend to the institutional dimension since this professional has the resources to support the school in understanding and working pedagogically with the students. In addition, it is considered that the Coordination Service at the system level is responsible for promoting actions that provide psycho-pedagogues from different schools with conditions for the collective analysis of their teaching processes. Based on these considerations, we report on successful experiences of institutional psycho pedagogical interventions aimed at uncovering the causes of students' so-called learning difficulties and consolidating inclusive psycho-pedagogical projects.